CBCT and microscopic analysis of the incidence of second mesiobuccal canal of maxillary molars - Pardo, Milena del Carmen Pita; Nishiyama, Celso Kenji [UNESP]; Ponce, José Burgos; Albarracín, Max Laurent (My University, 2012)
Introduction: The objective of successful endodontic treatment is a complete chemical-mechanical cleaning of root canals and filling. Therefore, a root canal not located represents a possible cause of endodontic failure, due to lack of cleaning and filling. Objective: The aim of this study was to determine the incidence of second mesiobuccal (2MB) canal in mesiobuccal roots of maxillary molars, comparing the efficacy of three methods for their identification: Cone beam computed tomography (CBCT), clinical analysis (CA) and operating microscope (OM). Methods: The existence of the second mesiobuccal (2MB) canal was evaluated by two examiners in 42 first and second molars without pulp involvement. The teeth were subsequently evaluated by the three methods and later these mesiobuccal roots were sectioned at 3 and 7 mm from the apex in the axial plane and observed with a digital microscope. Results: Was revealed the real presence of 10 2MB canals (23.81%). Statistical analysis by McNemar test showed that there was no statistically significant difference (p < 0.05) in the efficacy of 2MB canals localization between the three methods. Conclusion: None of the three methods made possible the determination of the 2MB canal in all cases, however CBCT showed the better results.
Keywords: Cone-beam computed tomography; Dental pulp cavity; Microscopy; Molar tooth